Reconceptualizing Sight Words to Promote Students Public Speaking Skill - Arjulayana Arjulayana; Dyah Supraba Lastari (UICELL, 2022)
Pubic speaking is a fundamental skill in global era, since all sectors of businesses require the marketing to promote the business. This research is aimed to explain the sight words work for students public speaking skill. This qualitative approach with classroom action research design is used in this research, and the population is 3rd semester students of English department Universitas Muhammadiyah Tangerang with the total sample is 33 students. the data collection based on the 2 cycles of EFL classroom activity, and the instruments are observation, interview, and public speaking test. this result of this research shows; firstly, the sight words are effective to advocate students public speaking practice, due to the sight words are used as a media for teaching public speaking, and it enjoyable and organizable. Secondly, student’s public speaking need mode drilling with a new strategy from the instruction, and this sigh words are recommended to use. Thirdly, although sight words mostly used to teach younger students for vocabulary knowledge, but when it used for university students for speaking skill is powerful because students become enthusiastic and active during the classroom activity individually, while the instructor only need to give a clue of the sight words. Key words: Sight words, public speaking, Learning Media, CAR